Product and Service Quality to Inflict Customer Satisfaction and Loyalty of Bank Sahabat Sampoerna Kelapa Gading Branch - Valentine Theresia Simamora; Wahid Akbar Basudani (Jurnal Mandiri : Ilmu Pengetahuan, Seni, dan Teknologi, 2023)
Post-pandemic economic growth is a focus for the government where one of the steps taken is a policy related to bank interest rates to stimulate the growth of corporate and small medium enterprise loans. One of the banks that has a focus on providing corporate and small medium enterprise loans is Bank Sahabat Sampoerna. Tight competition in the banking world in helping efforts to grow the economy has triggered Bank Sahabat Samporna to provide the best quality products and services to its customers so that these customers receive satisfaction which then become loyal customers. The purpose of this study was to determine whether there is an influence of product and service quality on customer satisfaction and loyalty at Bank Sabahat Sampoerna Kelapa Gading Branch. Smart-PLS is used to implement the SEM method in this study. In this study, 100 customers who used credit services were sampled using the accidental sampling method, which falls under the category of non-probability sampling.The endogenous variables Customer Loyalty (Z) and Customer Satisfaction (Y) were found to be 0.417 and 0.433, respectively, in this study. This demonstrates that the endogenous inert variable Customer Satisfaction (Y) is weakly affected by 0.433 by the exogenous factors Product Quality (X1) and Service Quality (X2). In the interim, the endogenous dormant variable Customer Loyalty (Z) is weakly impacted by 0.417 by the exogenous variable Product Quality (X1) and Service Quality (X2) through the intervening variable Customer Satisfaction (Y).